Ten Big Ones: A Stephanie Plum Novel - Evanovich, Janet; Wilson, Laura; Audio Renaissance (Firm) (New York : Audio Renaissance, 2004)
She's accidentally destroyed a dozen cars. She's a target for every psycho and miscreant this side of the Jersey Turnpike. Her mother's convinced she'll end up dead... or worse, without a man. She's Stephanie Plum and she kick,s butt for a living!
Subtitle from container.
Unabridged.
Compact disc.
"Includes a bonus interview with the author."--Container.
"An Audio Renaissance audiobook from St. Martin's Press."--Container.
Produced by Laura Wilson.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women detectives -- Fiction -- New Jersey; Murder for hire -- Fiction; Bounty hunters -- Fiction; Witnesses -- Fiction; Audiobooks (Unabridged); Trenton (N.J.) -- Fiction; Mystery fiction